Strategic resilience: Exploring diversification's impact on R&D investment during economic crises - Thi Bao Chau Nguyen; Quoc Nghi Nguyen (Heliyon)
Background: This paper aims to investigate the impact of diversification on decisions regarding strategic and technological choices during the global financial crisis. Specifically, we examine how the sudden changes in the macroeconomic environment impact research and development (R&D) investment decisions in diversified firms compared to stand-alone firms during the crisis. Methods: This study uses a panel sample of US firms from 2004 to 2009, which includes the crisis years (2007–2009). The final sample has 3232 firm-year observations. We use cross-sectional time-series feasible generalized least squares regression models. Results: Our findings show that firms with a higher degree of diversification are more likely to sustain or even increase R&D investment during economic crises, contrary to the general trend of R&D cuts. The negative relationship between diversification and R&D becomes weaker in the crisis period compared to the pre-crisis period. Conclusion: Our research reveals a distinctive advantage conferred by diversification in the realm of financing and investment. It allows firms not only to withstand turbulent economic conditions, but also to actively augment their value creation by amplifying R&D investment during profound uncertainty. This highlights the strategic acumen of diversified firms, which position themselves not merely as passive entities enduring crises but as proactive creators of value in the midst of adversity. In the continuously shifting terrain of corporate economics, these insights serve as a guiding light, directing firms towards strategies that not only shield them from crises, but also empower them to flourish and innovate, even during the most formidable challenges.